Penilaian Kondisi Terumbu Karang Di Area Perairan Dangkal Tanjung Pantai Senggigi, Lombok Barat, Nusa Tenggara Barat - Himawan, Mahardika Rizqi; Hariadi, Muhammad Dipa; Pratama, Alfian; Lestariningsih, Wiwid Andriyani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
This study aims to assess the condition of coral reefs based on benthic composition in the shallow waters of Tanjung, Senggigi Beach, West Lombok, West Nusa Tenggara. Data collection was carried out through diving using the Underwater Photo Transect (UPT) method by analyzing 50 quadrat photos taken along a 50-meter transect line, processed with the CPCe software. The analysis revealed that live coral (Coral) was the most dominant benthic component, with an average cover of 91.38% Â± 13.72%, which falls under the "very good" category. Macroalgae and abiotic components such as sand and coral rubble were present but in very small proportions. The coral community was dominated by complex growth forms such as Acropora tabular, Acropora branching, Coral foliose, and Coral massive, which are known for their relatively fast growth and adaptability to clear water with stable substrates. These findings indicate that the reef ecosystem in the waters of Tanjung Senggigi is in very good condition and provide a scientific foundation for developing effective management and conservation strategies for the area.